The Religious Construction of Kiai on Pluralism and Multiculturalism - Muhammad Turhan Yani; Muhammad Ali Haidar; Warsono Warsono; FX Sri Sadewo (UIN Maulana Malik Ibrahim Malang, 2018)
The reality of plurality in the context of humanity is something that Allah Almighty has desired, and the human task is to nurture and develop mutual respect and appreciation among people (tolerant). In this regard, the purpose of this study is to explore and explain exactly what kind of religious construction of kiai pesantren about pluralism and multiculturalism, the basis of references used, because it is related to the kiai’s point of view in resolving social conflicts that sometimes occur in the community. The data research was collected through survey and depth interview with some kiai pesantren in East Java. Data analysis was conducted with qualitative narrative and through Forum Group Discussion (FGD). The result shows that the mapping of religious construction of kiai pesantren in East Java consists of (1) religious construction with inclusive and exclusive categories and (2) religious construction with exclusive categories. Realitas pluralitas dalam konteks kemanusiaan merupakan kehendak Allah SWT, tugas manusialah memelihara dan mengembangkan rasa saling menghormati dan menghargai sesama (toleran). Dalam hal ini, tujuan penelitian ini mengeksplorasi dan menjelaskan dengan tepat konstruksi religius kiai pesantren tentang pluralisme dan multikulturalisme, dasar referensi yang digunakan, karena ini terkait dengan sudut pandang Kiai dalam menyelesaikan konflik sosial yang kadang-kadang terjadi di masyarakat. Pengumpulan data dilakukan melalui survei dan wawancara mendalam dengan beberapa kiai pesantren di Jawa Timur. Analisis data dilakukan dengan narasi kualitatif dan melalui Forum Group Discussion (FGD). Hasil penelitian menunjukan bahwa pembangunan agama Pesantren Kiai di Jawa Timur pada pluralisme dan multikulturalisme dapat dipetakan menjadi dua, yaitu (1) konstruksi keagamaan dengan kategori inklusif dan eksklusif dan (2) konstruksi keagamaan dengan kategori eksklusif.